Wordwall-Based Educational Games to Stimulate Symbolic Thinking Abilities Child - Rejabbilaisyah; Fitri April Yanti; Nesna Agustriana; Rendy Wikrama Wardana (Jurnal Ilmiah Pendidikan Profesi Guru, 2024)
The cognitive ability to think symbolically is essential for children's development. However, many teachers still need to provide more stimulation to young children's cognitive ability to think symbolically. This research aims to develop Wordwall-based educational game media and test its suitability as a learning medium to stimulate children's symbolic thinking abilities. This research uses the Research and Development (R&D) method with the development model from Borg and Gall. The research subjects were learning media experts, learning material experts, and kindergarten teachers. The test subjects, namely the trial, consisted of 9 children. The methods used to collect data are questionnaires and observations. The instruments used to collect data were questionnaire sheets and observation sheets. The techniques used to analyze data are qualitative and quantitative descriptive analysis. The research results, namely the results of assessments from media experts, material experts, and teacher assessments, obtained a level of validity in the very appropriate category. The results of child observations also show that this word wall-based educational game media effectively stimulates cognitive development for children aged 5-6 years. It was concluded that Wordwall-based educational game media can boost children's symbolic thinking abilities. The implications of the research are to contribute to the field of early childhood education, especially in developing innovative and effective learning methods to stimulate symbolic thinking abilities.